Description of a new genera and notes about the Neotropical genus Ceratinoptea Brunner von Wattenwyl (Blattodea: Pseudophyllodromiidae) in México - Estrada Álvarez, Julio Cesar; Sormani, Carlo Gilbert (Instituto de Ecología, A.C., 2024)
A new genus and species of cockroaches are described for the Mexican Neotropics, transferring two previously described species to the new genus and proposing a new synonymy between the species Temnopteryx otomius Saussure, 1868 and Aglaopteryx chiapas Fisk, 1977; In addition, new taxonomic and biogeographic data on the genus Ceratinoptera Brunner von Wattenwyl are provided.